Implementasi Manajemen Resiko Dalam Peningkatan Efektivitas Pembelajaran Di Sekolah Menengah Kejuruan - Sri Wulanjuni; Irsyad; Tia Ayu Ningrum (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
This study aims to find out about the application of risk management at SMK Mondoroko which includes determining the risk context, conducting a risk assessment consisting of Risk Identification, Risk analysis, and Risk Evaluation and determining mitigation in the learning process. This study uses a qualitative method approach with an exploratory analysis level that has been adapted to the stages in the risk management process from the ISO 31000:2018 framework on Risk Management Standards. Data was collected by observation, documentation and interviews with expert sampling. The results showed that risk analysis in the learning process at SMK Mondoroko was viewed from 4 categories, namely the student category, the teacher category, the curriculum category and the academic environment category. Based on these four categories, 29 risks were identified in the risk assessment process and had a significant impact sequentially, namely the curriculum category was handled through link and match curriculum synchronization with DUDI, the student category was handled through the application of work based learning (WBL) methods, the teacher category handling is carried out through the implementation of the industrial apprentice teacher program and the academic environment category is handled through the management and procurement of workshop equipment in accordance with the latest technology.